(untitled) (Research, Society and Development, 2021)
Passive and chronic exposure to tobacco smoke is a major cause of preventable diseases in humans and animals. The aim of this study was to evaluate the physiological and biochemical effects of functional foods: probiotics, prebiotics, and symbiotics in young rats exposed chronically to cigarette smoke. Ninety-six young male rats were randomly assigned to eight groups (n = 12): control (C); probiotic (Pro); prebiotic (Pre); symbiotic (Sym); smoking control (CS); smoking probiotic (ProbS); smoking prebiotic (PrebS); and smoking symbiotic (SymbS). After the experimental period of 189 days, the animals were anesthetized, blood samples were collected, and the animals were euthanized by exsanguination. The data were submitted to the Shapiro Wilk test, followed by the one-way ANOVA test, with contrasts by the Tukey method (P<0.05). The results demonstrated that chronic passive exposure to cigarette smoke had deleterious effects on the animals, and that these effects were attenuated in groups of animals supplemented with functional foods. In the supplemented groups there were significant improvements in weight gain, and mean values of liver enzymes (ALT, AST, GGT, and ALP), serum proteins (albumin and globulins), blood glucose, uremia, and creatininemia. We conclude that functional foods, probiotics, prebiotics, and symbiotics, attenuate the deleterious effects on the physiological and biochemical parameters of rats chronically exposed to cigarette smoke.